The Bacterial Mucosal Immunotherapy MV130 Protects Against SARS-CoV-2 Infection and Improves COVID-19 Vaccines Immunogenicity - del Fresno, Carlos; García-Arriaza, Juan; Martínez-Cano, Sarai; Heras-Murillo, Ignacio; Jarit-Cabanillas, Aitor; Amores-Iniesta, Joaquín; Brandi, Paola; Dunphy, Gillian; Suay-Corredera, Carmen; Pricolo, Maria Rosaria; Vicente, Natalia; López-Perrote, Andrés; et al. (Frontiers in Immunology, 2021)
COVID-19-specific vaccines are efficient prophylactic weapons against SARS-CoV-2 virus. However, boosting innate responses may represent an innovative way to immediately fight future emerging viral infections or boost vaccines. MV130 is a mucosal immunotherapy, based on a mixture of whole heat-inactivated bacteria, that has shown clinical efficacy against recurrent viral respiratory infections. Herein, we show that the prophylactic intranasal administration of this immunotherapy confers heterologous protection against SARS-CoV-2 infection in susceptible K18-hACE2 mice. Furthermore, in C57BL/6 mice, prophylactic administration of MV130 improves the immunogenicity of two different COVID-19 vaccine formulations targeting the SARS-CoV-2 spike (S) protein, inoculated either intramuscularly or intranasally. Independently of the vaccine candidate and vaccination route used, intranasal prophylaxis with MV130 boosted S-specific responses, including CD8+-T cell activation and the production of S-specific mucosal IgA antibodies. Therefore, the bacterial mucosal immunotherapy MV130 protects against SARS-CoV-2 infection and improves COVID-19 vaccines immunogenicity.